2010
DOI: 10.1016/j.semcdb.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligases in ErbB receptor quantity control

Abstract: Signaling through ErbB family growth factor receptor tyrosine kinases is necessary for the development and homeostasis of a wide variety of tissue types. However, the intensity of receptormediated cellular signaling must fall within a precise range; insufficient signaling can lead to developmental abnormalities or tissue atrophy, while over-signaling can lead to hyperplastic and ultimately neoplastic events. While a plethora of mechanisms have been described that regulate downstream signaling events, it appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 108 publications
1
44
0
Order By: Relevance
“…Nrdp1⌬cc lacks the coiled-coil domain but contains the RING finger, B-box, and ErbB3 binding domains. Nrdp1-32 encodes a naturally occurring splice variant lacking the RING finger and B-box domains and acts as a dominant negative to stabilize ErbB3 (13,16,17); the Nrdp1-32⌬cc derivative also lacks the coiled-coil region. Finally, Nrdp1-CSHQ is a double point mutant in zinc-binding residues 34 and 36 of the RING finger domain that lacks ligase activity (32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nrdp1⌬cc lacks the coiled-coil domain but contains the RING finger, B-box, and ErbB3 binding domains. Nrdp1-32 encodes a naturally occurring splice variant lacking the RING finger and B-box domains and acts as a dominant negative to stabilize ErbB3 (13,16,17); the Nrdp1-32⌬cc derivative also lacks the coiled-coil region. Finally, Nrdp1-CSHQ is a double point mutant in zinc-binding residues 34 and 36 of the RING finger domain that lacks ligase activity (32).…”
Section: Resultsmentioning
confidence: 99%
“…Although amplification of genes encoding the related EGFR and ErbB2 proteins correlates with the overexpression of these proteins in a variety of tumor types (7)(8)(9), erbb3 amplification does not appear to play a significant role in ErbB3 protein overexpression in tumors (7,10,11). Importantly, ErbB3 protein levels increase 10 -50-fold in tumors relative to surrounding normal tissue in a mouse model of ErbB2 overexpression-induced breast cancer and that difference cannot be accounted for by differences in transcript abundance (12)(13)(14)(15)(16). These observations underscore key roles for the dysregulation of posttranscriptional processes such as protein degradation in creating a permissive environment for ErbB3 protein overexpression in breast tumors.…”
mentioning
confidence: 99%
“…While gene expression certainly contributes to receptor homeostasis, accumulating evidence suggests that posttranscriptional mechanisms play key roles in determining cellular receptor tyrosine kinase levels (12). Importantly, protein degradation is emerging as a primary mechanism by which cells govern receptor quantity (6).…”
mentioning
confidence: 99%
“…This efficiency is often dramatically increased upon growth factor stimulation, leading to negativefeedback regulation of receptors and the suppression of further signaling (30). Endosomal sorting of receptors is thought to be carried out by E3 ubiquitin ligases, which physically associate with receptors to mediate their ubiquitination and ultimate trafficking to lysosomes (6). An example is Cbl, a particularly well characterized ubiquitin ligase whose recruitment to and ubiquitination of phosphorylated epidermal growth factor receptor (EGFR) is thought to be responsible for receptor downregulation following ligand stimulation (10,32).…”
mentioning
confidence: 99%
“…However, in breast cancer research Nrdp1 comes into focus because of its function in specifically suppressing cellular ErbB3 levels by proteolytic degradation [11][12][13][14][15][16][17]. Some reports showed that ErbB3 overexpression associated with poor prognosis in breast cancer patients [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%